Pengaruh E-Service Quality Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Mediasi pada J&T Cargo Kapten Regug - Agung Risma Dewi, I Gusti Putu; Artyanti Putri, Putu Riana (Economic Reviews Journal, 2025)
In the increasingly competitive logistics industry, companies must develop competitive advantages through the improvement of digital service quality that delivers value and positive experiences for customers. High-quality technology-based services can create customer satisfaction and foster loyalty toward the company. This study aims to examine the effect of E-Service Quality on Customer Loyalty with Customer Satisfaction as a mediating variable at J&T Cargo Kapten Regug. This research employs a quantitative associative approach. Data were collected from 120 customers of J&T Cargo Kapten Regug who have used digital services such as the application, website, or online tracking system. The analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0 software. The results show that E-Service Quality has a positive and significant effect on Customer Loyalty. Moreover, E-Service Quality has a positive effect on Customer Satisfaction, and Customer Satisfaction positively affects Customer Loyalty. The findings also reveal that Customer Satisfaction partially mediates the relationship between E-Service Quality and Customer Loyalty. This study supports the Expectation Confirmation Model (ECM), which explains that satisfaction arises when service performance meets or exceeds customer expectations, and such satisfaction becomes the foundation for building customer loyalty toward J&T Cargo’s digital services.